Social Cognitive Theory Construct as a Determinant of Physical Activity in Older People - Elisabeth Gultom; Frans Manangsang; Ellen R.V Purba (JURNAL INFO KESEHATAN, 2026)
The aging process causes a decline in physical function that increases the risk of chronic diseases and reduces the quality of life among older people, while participation in physical activity programs remains low. Social Cognitive Theory (SCT), particularly self-efficacy, outcome expectancy, and self-regulation, is considered an important approach for understanding and improving physical activity behavior among older people. This study aims to analyze the influence of Social Cognitive Theory (SCT) constructs, including self-efficacy, outcome expectancy, and self-regulation, on the physical activity of the older people in the Ciptomulyo Community Health Center work area, Malang City. Method: This study used an observational analytical design with a cross-sectional approach among 374 older people individuals aged 60-85 years. Data were collected through online questionnaires and structured interviews. Results: The study found that 64.4% of the older people had low levels of physical activity. The results of the hypothesis analysis showed that self-efficacy had a positive and significant effect on outcome expectancy (β=0.413; p<0.001), self-regulation (β=0.508; p<0.001) and physical activity (β=0.263; p<0.001). Outcome expectancy also had a significant positive effect on self-regulation (β=0.309; p<0.001), and physical activity (β=0.207; p<0.001). In addition, self-regulation has a significant positive effect on physical activity (β = 0.264; p < 0.001). Conclusion: Self-efficacy, outcome expectations, and self-regulation are important determinants of increased physical activity among older people. SCT-based interventions can be an effective approach motivating and increasing physical activity participation among older people.